Imbalance Of Power : US Hegemony and International Order - Edited By Zartman, I. William (New Dehli Viva Books, 2011)
Now that the clear delineations of the Cold War era are behind us, what are the contours of the international system? And what does the new reality mean for the United States, the acknowledged hegemon? Provocatively applying IR theory to the world of policy analysis, Imbalance of Power showcases current policy debates about the nature of both the international order and the role of the US within it. The authors bring to life concepts of realism, hegemony, liberalism, and constructivism, making it clear why these ideas are so relevant to understanding the challenges of world politics today. In the process, they address thorny issues of structure vs. policy, context vs. content, even determinism vs. choice - shedding light on the shape of a seemingly amorphous system."--Publisher's description.
Include Index,Bibliography and the Constributors.
Keywords: United States -- Foreign relations -- 2001- -- World Politics